2020
DOI: 10.1136/bjophthalmol-2020-316888
|View full text |Cite
|
Sign up to set email alerts
|

Two-year outcomes of the MINIject drainage system for uncontrolled glaucoma from the STAR-I first-in-human trial

Abstract: Background/AimsThe current study evaluates the efficacy and safety of the stand-alone implantation of the MINIject (iSTAR Medical, Wavre, Belgium) supraciliary, microinvasive glaucoma drainage device in patients with medically uncontrolled open-angle glaucoma.MethodsThis prospective, multicentre, first-in-human, single-arm interventional study evaluated stand-alone, ab interno implantation in 25 patients of a 5 mm long uveoscleral device made of STAR biocompatible material, which is a soft, microporous, flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 28 publications
0
30
0
1
Order By: Relevance
“…[266,267] Precision porous polymers with pores in 30-40 µm range have been used for a number of years as glaucoma draining devices to reduce intraocular pressure. [268] A vascular prosthesis that heals without the fibrotic sheath that impedes graft mechanical compliance is now in clinical trials (Evaluation of STARgraft AV for Hemodialysis Access, Clinical-Trials.gov Identifier: NCT03916731). Implanted glucose sensors fail in providing accurate, long-term glucose measurements, probably due to fibrotic blockage of the sensing element.…”
Section: Translation Of New Biocompatibility Concepts From Lab To Clinicmentioning
confidence: 99%
“…[266,267] Precision porous polymers with pores in 30-40 µm range have been used for a number of years as glaucoma draining devices to reduce intraocular pressure. [268] A vascular prosthesis that heals without the fibrotic sheath that impedes graft mechanical compliance is now in clinical trials (Evaluation of STARgraft AV for Hemodialysis Access, Clinical-Trials.gov Identifier: NCT03916731). Implanted glucose sensors fail in providing accurate, long-term glucose measurements, probably due to fibrotic blockage of the sensing element.…”
Section: Translation Of New Biocompatibility Concepts From Lab To Clinicmentioning
confidence: 99%
“…Perhaps the most frequently employed porogen leaching method for researching the effect of porosity on biocompatibility is sphere templating (Figure 2A). [4,9,10,[38][39][40][41][42][43] Devices including hemodialysis grafts [44] and supraciliary drainage implants for glaucoma treatment [45,46] are fabricated using sphere templating, illustrating the translatability of this method. Sphere templating is a subtractive method which creates pores by first forming an array of sintered sphere microparticles, then filling the spaces of the array with polymer precursors, solidifying the polymer, and finally removing the beads so that just the polymer scaffold remains.…”
Section: Subtractive Methodsmentioning
confidence: 99%
“…[ 45,46,48,289 ] In a recent clinical trial, the MINIject implant was found to effectively reduce intraocular pressure and reduce the need for medications across the two year study, without any serious adverse events. [ 46 ]…”
Section: Tissue‐specific Applications Of Porous Biomaterialsmentioning
confidence: 99%
“…The MINIject (iSTAR Medical) is an ab interno supraciliary device made of the STAR biocompatible material, which is a soft, microporous and flexible silicone. 218 It is 5 mm long and is oblong, 1.1 mm by 0.6 mm in cross-section, with a green ring at 0.5 mm for accurate AC positioning. The first human study showed a 40.7% reduction in IOP and a 47.6%/100% complete/ qualified success at 2 years with a 5% reduction in ECD.…”
Section: Minijectmentioning
confidence: 99%
“…The first human study showed a 40.7% reduction in IOP and a 47.6%/100% complete/ qualified success at 2 years with a 5% reduction in ECD. 218…”
Section: Minijectmentioning
confidence: 99%